THE LIVING QUR’AN: Desain Penelitian Studi Al-Quran Berbasis Etnografi - Darlis . (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2025)
The Living Qur'an as a research model for Qur'anic studies in Indonesia has been very dynamic. Since its first appearance in 2005 at the Sunan Kalijaga State Islamic University (UIN) in Yogyakarta, this research model has received a very positive response among Qur'anic scholars. A number of academic works, both books and journals, have been published on the Living Qur'an. However, the Living Qur'an research model is considered still immature both epistemologically and methodologically. This paper aims to discuss the ethnography-based Living Qur'an research design. Through a content analysis of several related books and articles, this paper demonstrates that an ethnographic approach in the study of the Living Qur'an is crucial and helps researchers to better understand the meaning of each Qur'anic behavior in society. Ethnography, as part of anthropology, assumes that humans are animal symbolicum, or animals capable of using, creating, and developing symbols to convey messages from one individual to another through language. In this context, ethnography requires Living Qur'an researchers not only to produce general knowledge about cultural practices related to the Qur'an, but also requires intimate interactions that can help understand the symbolic meaning of community behavior.